Inhibition of Sodium-GlucoseCotransporter 2 with Dapagliflozin in Han: SPRD Rats with Polycystic Kidney Disease - Daniel Rodriguez (Kidney & Blood Pressure Research, 2015)
Background/Aims: Dapagliflozin (DAPA) is a selective inhibitor of the sodium-glucose cotransporter 2 (SGLT2) which induces glucosuria and osmotic diuresis. The therapeutic effect of DAPA in progressing stages of polycystic kidney disease (PKD) has not been studied. Methods: We examined the effect of DAPA in the Han: SPRD rat model of PKD. DAPA (10 mg/kg/day) or vehicle (VEH) was administered orally via gavage to 5 week old male Han: SPRD (Cy/+) or control (+/+) rats (n = 8-9 per group) for 5 weeks. Blood and urine were collected at baseline and after 2.5 and 5 weeks of treatment to assess renal function and albuminuria. At the end of the treatment, rats were sacrificed and kidneys were excised for histological analysis. Results: After 5 weeks of treatment, DAPA-treated Cy/+ and +/+ rats exhibited significantly higher glucosuria, water intake and urine output than VEH-treated rats. DAPA-treated Cy/+ rats also exhibited significantly higher clearances for creatinine and BUN and less albuminuria than VEH-treated Cy/+ rats. DAPA treatment for 5 weeks resulted in a significant increase of the kidney weight in Cy/+ rats but no change in cyst growth. The degree of tubular epithelial cell proliferation, macrophage infiltration and interstitial fibrosis was also similar in DAPA-and VEH-treated Cy/+ rats. Conclusion: The induction of glucosuria with the SGLT2-specific inhibitor DAPA was associated with improved renal function and decreased albuminuria, but had no effect on cyst growth in Cy/+ rats. Overall the beneficial effects of DAPA in this PKD model were weaker than the previously described effects of the combined SGLT1/2 inhibitor phlorizin.